Understanding the Importance of “Symbolic Interaction Stigma:” How Expectations about the Reactions of Others Adds to the Burden of Mental illness Stigma - Link, Bruce G. (Psychiatr Rehabil J, 2015)
OBJECTIVE: Important components of stigma include imagining what others might think of a stigmatized status, anticipating what might transpire in an interaction with others, and rehearsing what one might do if something untoward occurs. These imagined relations are here called “symbolic interaction stigma” and can be impactful even if the internalization of negative stereotypes fails to occur. Concepts and measures that capture symbolic interaction stigma are introduced and a preliminary assessment of their impact provided. METHODS: Four self-report measures of symbolic interaction stigma (perceived devaluation discrimination, anticipation of rejection, stigma consciousness and concern with staying in) were developed or adapted and administered to a sample of individuals who have experienced mental illness (N=65). Regression analyses examined whether forms of symbolic interaction stigma were associated with withdrawal, self-esteem and isolation from relatives independent of measures of internalization of stigma and rejection experiences. RESULTS: As evidenced by scores on four distinct measures symbolic interaction stigma was relatively common in the sample, somewhat more common than the internalization of stigma. Additionally, measures of symbolic interaction stigma were significantly associated with withdrawal, self-esteem and isolation from relatives even when a measure of the internalization of stigma was statistically controlled. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: The study suggests the potential importance of considering symbolic interaction forms of stigma in understanding and addressing stigma and its consequences. Being aware of symbolic interaction stigma could be useful in enhancing rehabilitation goals if an approach to counteracting the negative effects of these aspects of stigma can be developed.